RESOURCE MANAGEMENT STRATEGIES TO IMPROVE EDUCATION QUALITY IN PRIMARY SCHOOLS - Mulyadi; Darry Christine S. Purba; Farida Asy'ari; Al-Amin (CV. ADIBA AISHA AMIRA, 2024)
Effective resource management strategies are key to improving the quality of education in primary schools. Continuous development of teachers' capacity through training programs in line with curriculum needs and the use of the latest educational technology play a vital role in enriching students' learning experience. Improved school infrastructure such as conducive classrooms, updated laboratories and well-stocked libraries support more efficient and interactive teaching and learning. Collaboration with parents and the school site community is equally important, through mobilizing additional support and resources, which in turn, improves student motivation and learning outcomes. The research method used in this study is the literature research method. The results show that continuous professional development for teachers is a dominant factor in improving the quality of learning. Effective programs include customized training that is integrated with current educational needs and objectives. Adequate educational infrastructure and access to educational technology also play an important role in creating an efficient learning environment and encouraging students to perform better academically. Finally, parental and community involvement was found to be a key aspect in enhancing students' learning motivation and sustaining the school's efforts in providing educational resources. It also strengthens the school's relationship with external stakeholders and helps in the mobilization of additional resources